Distinct chromatin structures at the monoamine oxidase‐A promoter correlate with allele‐specific expression in SH‐SY5Y cells. (11th May 2018) - Manca, M.; Pessoa, V.; Myers, P.; Pickles, A.; Hill, J.; Sharp, H.; Murgatroyd, C.; Bubb, V. J.; Quinn, J. P.
Abstract : Monoamine oxidase‐A (MAOA) metabolises monoamines and is implicated in the pathophysiology of psychiatric disorders. A polymorphic repetitive DNA domain, termed the uVNTR (upstream variable number tandem repeat), located at the promoter of the MAOA gene is a risk factor for many of these disorders. MAOA is on the X chromosome suggesting gender could play a role in regulation. We analysed MAOA regulation in the human female cell line, SH‐SY5Y, which is polymorphic for the uVNTR. This heterozygosity allowed us to correlate allele‐specific gene expression with allele‐specific transcription factor binding and epigenetic marks for MAOA. Gene regulation was analysed under basal conditions and in response to the mood stabiliser sodium valproate. Both alleles were transcriptionally active under basal growth conditions; however, the alleles showed distinct transcription factor binding and epigenetic marks at their respective promoters. Exposure of the cells to sodium valproate resulted in differential allelic expression which correlated with allele‐specific changes in distinct transcription factor binding and epigenetic marks at the region encompassing the uVNTR. Biochemically our model for MAOA promoter function has implications for gender differences in gene × environment responses in which the uVNTR has been implicated as a genetic risk. Abstract :